Digestive propensity of Aflatoxin M1 (4‐Hydroxyaflatoxin B1), an indication from in vitro digestion model system. Issue 5 (5th April 2022) - Kumar, Lal Krishan; Kapri, Ankita; Chandel, Rajeev; Kumar, Varun; Verma, Suryakant; Vedamurthy, Gowdar Veerappa; Singh, Dheer; Onteru, Suneel Kumar
Abstract: Milk quality and safety maintenance is an important issue, as many reports showed several biological and chemical contaminants in the milk. Among all contaminants, AFM1 is detected frequently in milk samples. Therefore, our main aim was to understand the digestive fate of AFM1 in an in vitro digestion (IVD) model system by using AFM1 spiked milk samples (2 μg/L). The IVD of the milk was confirmed by SDS‐PAGE and AFM1 was estimated with ELISA. ELISA results confirmed that AFM1 was detected only in the spiked undigested milk samples, but not in IVD control and spiked milk samples. This observation clearly shows that AFM1 was digested during IVD. We also assessed AFM1 at different stages of digestion and found that AFM1 was digested only at the pancreatic digestion stage. In conclusion, the present study indicates that AFM1 at 2 ug/L in the milk might be completely digested. Novelty impact statement: 'Aflatoxin M1 appears to be digested by pancreatic juice, especially by the lipase'.